Novel access to epilupeol through chemoselective hydrogenation of lupenone using platinum-based organotin catalysts - Castro, Maria Julia (2018)
Catalytic hydrogenation of terpenes constitutes one of the most interesting reactions in the transformation of natural products. One of the key goals in this synthesis is the selective hydrogenation of the CO bond for obtaining biologically active epimeric alcohols. In the present work, the use of Pt and PtSn catalysts supported on silica was studied as an alternative to the chemoselective hydrogenation of lupenone. It was observed that Sn produces geometric and electronic modifications that lead to improvement in the chemo- and stereoselectivity of the desired product.